Bringing home the housing crisis : politics, precarity and domicide in austerity London - Nowicki, Mel (Book collections on Project MUSE., 2023)
Often portrayed as an apolitical space, this book demonstrates that home is in fact a highly political concept. This book explores the legislative changes dismantling vulnerable groups' rights to decent and affordable housing.